STUDI KOMPARASI MINAT BERWIRAUSAHA SISWA KELAS XI JURUSAN AKUNTANSI DAN JURUSAN PEMASARAN - Yanti, Eka Dwi; Matsum, Junaidi H; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research was comparative study on entrepreneurship interest on students in accounting major and marketing major grade XI at SMK Negeri 3 Pontianak.Â  The problem in this research was whether there were entrepreneurship interest on students of accounting major and students of marketing major at SMK Negeri 3 Pontianak. The method in this research was descriptive comparative with the form of research ex post facto. The sample of this research was 60 students. The data obtained by using direct communication techniques by interviewing the teacher who taught entrepreneurship major. The direct communication techniques by using questionnaire and dokumenter study techniques with the data or documents. Based on the data analysis, the t result showed that the value of tcount < t table (0,050 < 2,001) with significance (0,960 > 0,05) in hence, Ho was accepted and Ha was rejected. Thus, it can be conlcuded that there is no entrepreneurship interest differences on the students of accounting and markering major in grade XI at SMK Negeri 3 Pontianak.Â Keywords: Entreprenuership Interest, The Students of Entrepreneurship, The Student of Marketing Major